APLIKASI ERP SEBAGAI ALAT BANTU ACCOUNTING INFORMATION SYSTEM DI DALAM MENGOPTIMALKAN FUNGSI KONTROL ATAS AKTIVITAS PERUSAHAAN - Purwanto (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2015)
ABSTRACT : Accounting Information Systems ( AIS ) is a formal information systems , has a purpose , phases , tasks , resources differences the Company's activity covers for whole hearts provision of information to all users in the company. Company's activities include the revenue cycle , expenditure cycle, production cycle , human resources cycle, general ledger and reporting system; and one of the technology role integrating each company functions is Enterprise Resource Planning ( ERP ) . ERP application control functions run more optimal , or any weaknesses minimized the possibility of cheating can avoided.